Mechanisms of Salmonella typhimurium Resistance to Cannabidiol - Iddrisu Ibrahim; Joseph Atia Ayariga; Junhuan Xu; Daniel A. Abugri; Robertson K. Boakai; Olufemi S. Ajayi (Microorganisms)
The emergence of multi-drug resistance (MDR) poses a huge risk to public health globally. Yet these recalcitrant pathogens continue to rise in incidence rate with resistance rates significantly outpacing the speed of antibiotic development. This therefore presents related health issues such as untreatable nosocomial infections arising from organ transplants and surgeries, as well as community-acquired infections that are related to people with compromised immunity, e.g., diabetic and HIV patients, etc. There is a global effort to fight MRD pathogens spearheaded by the World Health Organization, thus calling for research into novel antimicrobial agents to fight multiple drug resistance. Previously, our laboratory demonstrated that Cannabidiol (CBD) is an effective antimicrobial against Salmonella typhimurium (S. typhimurium). However, we observed resistance development over time. To understand the mechanisms S. typhimurium uses to develop resistance to CBD, we studied the abundance of bacteria lipopolysaccharide (LPS) and membrane sterols of both CBD-susceptible and CBD-resistant S. typhimurium strains. Using real-time quantitative polymerase chain reaction (rt qPCR), we also analyzed the expression of selected genes known for aiding resistance development in S. typhimurium. We found a significantly higher expression of blaTEM (over 150 mRNA expression) representing over 55% of all the genes considered in the study, fimA (over 12 mRNA expression), fimZ (over 55 mRNA expression), and integron 2 (over 1.5 mRNA expression) in the CBD-resistant bacteria, and these were also accompanied by a shift in abundance in cell surface molecules such as LPS at 1.76 nm, ergosterols at 1.03 nm, oleic acid at 0.10 nm and MPPSE at 2.25nm. For the first time, we demonstrated that CBD-resistance development in S. typhimurium might be caused by several structural and genetic factors. These structural factors demonstrated here include LPS and cell membrane sterols, which showed significant differences in abundances on the bacterial cell surfaces between the CBD-resistant and CBD-susceptible strains of S. typhimurium. Specific key genetic elements implicated for the resistance development investigated included fimA, fimZ, int2, ompC, blaTEM, DNA recombinase (STM0716), leucine-responsive transcriptional regulator (lrp/STM0959), and the spy gene of S. typhimurium. In this study, we revealed that blaTEM might be the highest contributor to CBD-resistance, indicating the potential gene to target in developing agents against CBD-resistant S. typhimurium strains.